The Spatial Agglomeration and Industrial Network of Strategic Emerging Industries and Their Impact on Urban Growth in Mainland China. (31st August 2021) - Li, Jiaming; Zhang, Peiyuan; He, Jialin; Sun, Dongqi
Abstract : Strategic emerging industries (SEIs) are an important industrial policy to promote innovation, develop advanced manufacturing, and upgrade the economy in China. The research explores the impact of SEIs on urban economic growth in mainland China, from agglomeration externalities and network externalities. The results show that SEIs have a significant impact on growth, and network externalities are generally more important than agglomeration externalities. Although the agglomeration of large-scale listed enterprises in the city promotes growth, too many large enterprises in the cluster, that is, the lack of small and medium-sized supporting enterprises, will harm urban growth. Meanwhile, a city with a higher degree of centrality has a larger GDP, but the strength has a negative impact.